A Regional right against air pollution : the applicability of the requirement to exhaust local remedies in the context of the right to a clean and healthy environment under the African charter - Mohamed, Amina Amran (Strathmore University, 2017)
Human rights appear to have different implications amongst different peoples predicated upon their particular political, religious, social, and cultural settings. The European Court of Human Rights in Lautsi and Others v Italy propounded that to establish a uniform application of human rights would be against the foundational purpose of those human rights it seeks to protect as it would purport to impose a uniform culture and thus freeze cultural practices in status quo. It is against the backdrop of this realisation that the margin of appreciation was introduced by the European Commission and later adopted by the African Commission, in order to accommodate such diversities by providing for a ‘contextualised implementation’ of human rights. The margin of appreciation refers to the leeway that International organisation grant national authorities, in fulfilling their obligations under Human Rights Conventions. This approach has since been acknowledged to be manifested, cardinally, in the duty to exhaust local remedies under article 56(5) of the African Charter on Human and Peoples’ Rights. The purpose for which is to allow the respondent state an opportunity to redress, by its own means, within the framework of its own domestic legal system the wrong alleged to have been done to the individual. This study seeks to interrogate the applicability of the duty to exhaust local remedies to the right to a clean and healthy environment. As such, the study will evaluate the limitations on the applicability of the requirement to exhaust local remedies in the context of the right to a clean and healthy environment under the African Charter. The study proceeds from the approach that the right to a clean and healthy environment is trans-national in character and therefore outside the scope of the margin of appreciation of state parties. Such analysis will, however, be specific to air pollution due to the acknowledgement that it is a universal facet, although not exclusively so, of this right.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree at Strathmore University Law School
Keywords: Human rights; European Court of Human Rights; African Charter on Human and Peoples’ Rights